English English - Muhammad Rifki Shihab; Annisa Sajidah (AI Society & STMIK Indonesia, 2024)
Current technological developments encourage companies to re-evaluate their organizational business models to take advantage of technological advances. This research explores the impact of information technology in business model transformation at peer-to-peer lending company. PT XYZ is one of a financial technology (fintech) company in Indonesia which was originally engaged in the traditional lending and borrowing business and then transformed into peer-to-peer lending and then developed Supply Chain Financing (SCF) with a Business to Business (B2B) scheme which was previously only done by banks. The IT Impact Map analysis conducted in this study shows this company’s strategic transformation in adopting technology, IT has an impact on company strategy and value through business process reengineering and allows companies to capture new opportunities.